Rare-Earth Doped Hydroxyapatite Nanoparticles for Biomedical Applications: A Comprehensive Review From Bone Regeneration to Cancer Theranostics - Kareem, Rebaz Obaid; Barzinjy, Azeez A.; Kaygili, Omer; Sienkiewicz, Jozef E.; Jasik, Patryk; Bulut, Niyazi (Wiley, 2026)
Rare-earth element (REE)-doped hydroxyapatite nanoparticles (HAp-NPs) have emerged as multifunctional bioceramics with significant potential across diverse biomedical fields, owing to their excellent biocompatibility, bioactivity, and tunable physicochemical properties. Recent advances in the doping of HAp-NPs with lanthanide ions have expanded their functionality, enabling innovative applications in bone tissue engineering, targeted drug delivery, cancer therapy, dentistry, and biomedical imaging. This review provides a comprehensive assessment of the synthesis strategies and surface modification techniques, utilizing both natural and synthetic precursors, for REE-doped HAp-NPs. Particular attention is given to the role of individual REE dopants (e.g., La3+, Ce3+, Pr3+, Eu3+, Gd3+, Er3+, Sm3+, Nd3+, Dy3+, Tb3+, Yb3+, and Y3+) in modulating the luminescent, antibacterial, osteoconductive, and drug-delivery properties of HAp-NPs. Furthermore, the theranostic potential of these nanomaterials is examined, emphasizing their low cytotoxicity, high loading capacity, efficient cellular uptake, and advanced imaging capabilities. Collectively, REE-doped HAp-NPs represent a versatile and promising platform for the development of next-generation nanomedicines, with broad implications for precision therapy and regenerative medicine.
Keywords: biomedical nanomaterials; bone regeneration; cancer theranostics; drug delivery systems; rare-earth doped hydroxyapatite